CdSe quantum dot-based nanocomposites for ultralow-power memristors - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Shankar, Uday; Rath, Arup Kumar; Sahu, Satyajit (ACS Applied Nano Materials, 2022)
The explosion in digital communication with the huge amount of data and the internet of things (IoT) led to the increasing demand for data storage technology with faster operation speed, high-density stacking, nonvolatility, and low power consumption for saving energy. Metal chalcogenide-based quantum dots (QDs) show excellent nonvolatile resistive memory behavior owing to their tunable electronic states and control in trap states by passivating the surface with different ligands. Here, we synthesized high-quality colloidal monodispersed CdSe QDs by the hot injection method. The CdSe QDs were blended with an organic polymer, poly(4-vinylpyridine) (PVP), to fabricate an Al\textbackslashCdSe-PVP\textbackslashAl device. Our device shows excellent bipolar nonvolatile resistive random access memory (RRAM) switching behavior with a high current ON/OFF ratio (I-ON/OFF) of 6.1 x 10(4), and it consumes ultralow power. The charge trapping and detrapping in the potential well formed by the CdSe QD and PVP combination result in resistive switching. This CdSe-PVP-based resistive random access memory (RRAM) device with a high I-ON/OFF, ultrafast switching speed, high endurance, low operating voltage, and long retention period can be used as a high-performance and ultralow-power memristive device.
Keywords: memory switching; memristor; metal chalcogenides; nonvolatile; quantum dots

Scanning tunneling microscopy investigation of synaptic behavior in AgInS2 quantum dots: effect of ion transport in neuromorphic applications - Betal, Atanu; Chetia, Anupam; Bera, Jayanta; Saikia, Dibyajyoti; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2024)
Scanning tunneling microscopy (STM) is a powerful technique for investigating the nanoscale properties of functional materials. Additionally, scanning tunneling spectroscopy (STS) facilitates the determination of the local density of states (LDOS) within the material. In this study, we present an exploration of the resistive switching (RS) properties and neuromorphic computing capabilities of individual AgInS2 quantum dots, utilizing STM and STS techniques. By examining the material's bandgap and its temperature dependence, we uncover a nonlinear variation below the Debye temperature and a linear trend at higher temperatures. Moreover, STS measurements demonstrate changes in the conducting states induced by localized pulses, further confirming the unique characteristics of the quantum dots. The experimental devices constructed by using these quantum dots effectively replicate the RS properties observed at the nanoscale. To assess the neuromorphic application of the devices, pulse transient measurements simulating the learning and forgetting processes were conducted. The gradual set and reset processes successfully mimic the information retention and erasure capabilities essential for neuromorphic computing. Notably, the resistive switching mechanism in these devices is attributed to localized ionic transport, which highlights the significant involvement of ionic species in the observed RS behavior. The outcomes of this study contribute to the fundamental understanding of RS properties in single AgInS2 quantum dots and offer valuable insights into their potential applications in neuromorphic computing.
Keywords: corona poling; Ion transport; neuromorphic computing; quantum dots; resistive switching; Scanning tunneling microscopy; STS